Flyback transformer leakage inductance energy absorption and feedback circuit - YU HONGBIN; ZHAO YI; YANG BO (2015)
A flyback transformer leakage inductance energy absorption and feedback circuit is characterized in that the leakage inductance energy absorption and feedback circuits are integrated together, the integrated circuit is composed of a clamper tube Sc and a clamping capacitors Cc, and is simple and reliable in structure. A control method of the flyback transformer leakage inductance energy absorption and feedback circuit is that the clamper tube is conducted for time Tc after a flyback main tube is turned off, and the Tc is a half of the resonance cycle of an leakage inductor and the clamping capacitor and is much less than the turn-off time of the main tube. By the resonance of the clamping capacitor and the leakage inductor, the leakage inductance energy absorbed by the clamping capacitor is released to a main power circuit, thereby reducing the turn-off voltage peak of a flyback circuit main tube effectively, and improving the efficiency of a flyback converter. Meanwhile, the conduction time of the clamper tube is much less than the turn-off time of the main tube because of the non-complementary conduction of the clamper tube and the main tube, so that the absorption and feedback circuit does not influence the on-off process of the main tube, and is suitable for a flyback circuit of any working mode. By adopting a miniature photovoltaic grid connected inverter of the scheme of the utility model, the reliability and efficiency of the circuit are both improved greatly.